Effects of dietary inclusion of alfalfa meal on laying performance, egg quality, intestinal morphology, caecal microbiota and metabolites in Zhuanghe Dagu chickens. Issue 1 (31st December 2022) - Cui, Yan; Diao, Zipeng; Fan, Wentao; Wei, Jiali; Zhou, Jiasheng; Zhu, Hongyan; Li, Desheng; Guo, Longwei; Tian, Yumin; Song, Hui; Su, Yuhong
Abstract: This study was conducted to investigate the effects of dietary inclusion of alfalfa meal (AM) on the productive performance of Zhuanghe Dagu chickens. A total of 288 35-week-age layers were randomly assigned into four dietary treatments in a 35-day trial. Dietary conditions were based on a basal diet and supplemented with 0, 3, 6, 9% AM (CON, AM3, AM6 and AM9). Results showed that dietary inclusion of AM had positive effects on the egg production rate, feed conversion ratio (FCR), egg mass, yolk colour, albumen height and haugh unit. In addition, the small intestinal morphology such as villus height, crypt width and muscular thickness were improved by including AM in the diet. AM supplementation enriched the microbiota diversity in the caecum. The Firmicutes / Bacteroidetes ratio has decreased, and the Synergistetes has increased in AM supplemented groups compared with the CON group. Predictive functional analysis revealed that metabolic pathways of carbohydrate, lipid, terpenoids and polyketides, etc. were significantly enriched in the experimental groups. A total of 397 differential metabolites have been identified between AM6 group and CON group. Among them, a total of 176 metabolites were upregulated and 221 metabolites were downregulated. Therefore, dietary inclusion of AM was beneficial to improve the laying performance, egg quality, small intestinal morphology, caecal microbiota diversity and caecal metabolic function in Zhuanghe Dagu chickens, with the optimum dose being 6%. Highlights: Feeding Dagu chickens with AM containing diet had beneficial effects on the productive performance Dietary inclusion of AM improved intestinal morphology parameters in Dagu chickens The nutritional metabolic function of Dagu chickens was positively affected by including AM